A casing containing a mullite strong and tough layer and a preparation method thereof

By designing multi -scale heterogeneous interface microstructures in porcelain sleeves, the use of Mo Lai Shi powder, ceramic balls and fibers to form a strong layer of tough layer, solving the problem of being easily fried and uniformly distributed by the existing porcelain sleeve tube to achieve The high toughness and reliability of the sleeve increase.

CN119039055BActive Publication Date: 2025-01-24NEI MENG GU CHAO GAO YA GONG DIAN JU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411524588.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing porcelain casing is prone to explosion and damage in the power grid, resulting in unstable operation of power supply facilities and safety hazards. When mullite is directly introduced as a toughening agent in the casing base, the toughening effect is limited, the distribution is uneven, and the stability is poor. .

Method used

Adopt a multi-scale heterogeneous interface micro-structural design idea, coat the strong tough layer and glazed layer by coating the tough layer and the glazed layer through the outer wall and inner wall of the tube. Composition of Lai Shi powder, Mo Lai Shi ceramic ball and Mo Lai Shi fiber, and prepared through spraying and sintering processes, forming a complex, continuous and multi -scale Mo Lai Stone combined network.

Benefits of technology

It significantly improves the toughness and reliability of the casing, forms a good bonding interface, delays crack expansion, improves the safety and stability of the casing, and overcomes the limitations of a single toughening strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039055B_ABST
    Figure CN119039055B_ABST
Patent Text Reader

Abstract

The invention discloses a casing containing a mullite tough layer and a preparation method thereof, comprising a casing blank of a hollow tubular structure, a tough layer composed of mullite powder, mullite ceramic balls and mullite fibers of different morphologies sprayed on the outer wall of the casing blank, a glaze layer sprayed on the side of the tough layer away from the casing blank, a glaze layer sprayed on the side wall of the casing blank away from the tough layer, the casing blank is dried to obtain a glaze blank, and the glaze blank is sintered at high temperature to obtain a casing containing a mullite tough layer. The invention mixes mullite powder, mullite ceramic balls and mullite fibers of different morphologies to obtain a tough layer forming a multi-scale, complex and continuous bonding network, and forms a good bonding interface with the casing blank, the crack extension process is conducive to the consumption of strain energy, improves toughness, and can effectively protect the casing blank during the casing explosion damage process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of power system equipment, and particularly relates to a casing containing a mullite tough layer and a preparation method thereof. Background Art

[0002] High-voltage bushings are devices that allow one or more conductors to pass through partitions such as walls or boxes, and serve as insulation and support. They are important equipment in power systems. Among various high-voltage bushings, porcelain bushings are the most commonly used. However, in recent years, the frequency of porcelain bushing explosion accidents in power grids has increased, threatening the normal operation of power supply facilities and the personal safety of workers.

[0003] At present, there are few and single studies on the toughening of ceramic sleeve materials, and the toughening methods or theories are mainly based on the research foundation of other ceramic materials or composite materials. Commonly used ceramic sleeve materials belong to the aluminum-silicon system, and the main chemical components are Al2O3 and SiO2. According to the Al2O3-SiO2 binary phase diagram, mullite is an important compound in the system, with good high temperature performance, mechanical properties, thermal shock resistance and a small thermal expansion coefficient. Mullite is easy to form a one-dimensional morphology, so it has become the most commonly used additive for strengthening and toughening aluminum-silicon ceramic materials.

[0004] However, the following technical problems still exist when directly introducing mullite into the raw material of the casing matrix to improve the toughness of the casing: First, the toughening effect is affected by the amount of toughening agent used, cost, degree of dispersion, and degree of combination with the casing raw material. It only has a significant strengthening effect on the casing and a limited toughening effect. Second, the growth conditions of mullite morphology are harsh, and the sintering process can easily lead to uneven distribution of mullite content and morphology differences inside the porcelain casing material, which deteriorates the stability of material performance. Third, the toughness of the material itself is not essentially improved, and only different process conditions and assembly structures are considered to improve the reliability of the overall equipment operation. When the use conditions change, the material itself is still difficult to meet the requirements for its toughness. Summary of the invention

[0005] In view of this, a first object of the present invention is to provide a casing containing a mullite toughening layer.

[0006] The second object of the present invention is to provide a method for preparing a casing containing a mullite toughening layer.

[0007] The first object of the present invention is implemented by the following technical scheme: a sleeve containing a mullite strengthening layer, comprising a sleeve blank with a hollow tubular structure, the outer wall of the sleeve blank is coated with a strengthening layer, the inner wall of the sleeve blank is coated with a glaze layer, and the side of the strengthening layer away from the sleeve blank is coated with a glaze layer; the strengthening layer is composed of mullite powder, mullite ceramic balls and mullite fibers in a mass ratio of 6:6-11:3-8.

[0008] Furthermore, the thickness of the tough layer is 2-5 mm.

[0009] The second object of the present invention is implemented by the following technical solution: a method for preparing a casing containing a mullite toughening layer, which specifically comprises the following steps:

[0010] S1: preparing a casing blank, wherein the raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and the casing blank is obtained by wet ball milling, spray granulation, cold isostatic pressing, blanking, and drying;

[0011] S2: Using silica sol as a binder, add 1.2-2.5% of sodium humate, 0.25-0.4% of polycarboxylic acid high-efficiency water reducer, 0.6-1.1% of hydroquinone, 0.2-0.35% of polyether modified silicone, and 0.3-0.6% of potassium sodium tartrate to the silica sol in sequence, and stir mechanically at a speed of 1500-2000 rpm for 10-15 minutes to obtain a premixed solution;

[0012] S3: adding mullite powder, mullite ceramic balls and mullite fibers in a mass ratio of 6:6-11:3-8 into the premixed solution, and mechanically stirring at a speed of 1500-2000 rpm for 10-20 min to obtain a tough layer slurry;

[0013] S4: spray the tough layer slurry evenly on the outer wall of the casing blank at a spraying rate of 30-50 cm / s and a spraying time of 30-50 min, and dry the sprayed casing at 50° C. for 24 h to obtain a casing blank containing a tough layer;

[0014] S5: spraying glaze inside and outside the sleeve blank containing the tough layer, and obtaining a glaze blank after drying;

[0015] S6: sintering the glaze blank at 1260°C-1300°C for 5-7 hours to obtain a sleeve containing a strong and tough layer.

[0016] Furthermore, the particle size of the mullite powder is 600-1000 mesh, the particle size of the mullite ceramic ball is 200-300 mesh, the monofilament diameter of the mullite fiber is 3-5um, and the short cut length is ≤1mm.

[0017] Furthermore, the mass ratio of the silica sol to the total weight of the mullite powder, the mullite ceramic balls and the mullite fibers is 1:5.

[0018] Furthermore, the spraying thickness of the toughening layer slurry is 2-5 mm.

[0019] Advantages of the present invention:

[0020] 1. The idea of ​​"multi-scale heterogeneous interface microstructure design" is introduced into the porcelain sleeve design. By mixing mullite powder, mullite ceramic balls and mullite fibers with different morphological characteristics, a complex, continuous, multi-scale mullite bonding network tough layer is formed, ensuring the stability of the introduced mullite phase and microscopic morphology.

[0021] 2. Mullite additives are used to prepare the tough layer raw materials instead of directly introducing them into the casing material matrix. On the one hand, it effectively improves the uneven distribution of components in the matrix when the additives are directly introduced, thereby improving the reliability of the casing; a good bonding interface can be formed between the tough layer and the casing blank. When the crack extends to the interface, the deflection, extension and branching of the crack at the interface can consume the power of crack extension, thereby improving the toughness of the material; on the other hand, the preparation of the tough layer in the casing improves the safety of the casing. When the casing bursts, the continuous network formed by the tough layer can effectively restrain the destruction of the casing blank and limit the explosion damage of the casing blank.

[0022] 3. The present invention simultaneously solves the physical phase composition design, microstructure design, and porcelain sleeve structure design of the casing, and improves the toughness of the casing under the synergistic effect from the physical phase composition to the macro-microstructure design, overcoming the enhancement effect of the casing strengthening effect under a single strategy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a schematic diagram of the structure of the mullite tough layer casing of the present invention;

[0025] In the figure, 1, sleeve body, 2, strengthening layer, 3, glaze layer. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the description of the present invention, it should be noted that the terms "center", "up", "down", "front", "back", "top", "bottom", "left", "right", "vertical", "horizontal", "inside" and "outside" etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limiting the present invention.

[0028] Embodiment 1:

[0029] like Figure 1 As shown, a sleeve containing a mullite strengthening layer comprises a sleeve blank 1 with a hollow tubular structure, the outer wall of the sleeve blank 1 is coated with a strengthening layer 2, the inner wall of the sleeve blank 1 is coated with a glaze layer 3, and the side of the strengthening layer 2 away from the sleeve blank 1 is coated with the glaze layer 3; the thickness of the strengthening layer 2 is 3 mm; the strengthening layer 2 is composed of mullite powder, mullite ceramic balls and mullite fibers in a mass ratio of 6:6-11:3-8, and the mass ratio of the mullite powder, mullite ceramic balls and mullite fibers contained in the strengthening layer 2 in this embodiment is 3:5:2.

[0030] The toughening layer 2 in this embodiment is composed of mullite powder, mullite ceramic balls, and mullite fibers with different morphological characteristics to form a complex, continuous, multi-scale mullite bonding network, which ensures the stability of the introduced mullite phase and micromorphology and improves the controllability of the introduced toughening phase composition and content.

[0031] The present embodiment provides a method for preparing a casing containing a mullite toughening layer, and the specific steps are as follows:

[0032] S1: The raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and the casing blank 1 is obtained by wet ball milling, spray granulation, cold isostatic pressing, blank trimming, and drying;

[0033] S2: Using silica sol as a binder, 2% of sodium humate, 0.3% of polycarboxylic acid high-efficiency water reducer, 0.8% of hydroquinone, 0.25% of polyether modified silicone, and 0.5% of potassium sodium tartrate were added to the silica sol in sequence, and mechanically stirred at 1800 rpm for 12 minutes to obtain a premixed solution;

[0034] S3: Mullite powder, mullite ceramic balls and mullite fibers are added to the obtained premixed solution in a mass ratio of 3:5:2, and mechanically stirred at a speed of 1800 rpm for 15 minutes to obtain a tough layer 2 slurry; wherein the mass ratio of silica sol to the total weight of mullite powder, mullite ceramic balls and mullite fibers is 1:5; the particle size of mullite powder is 800 mesh, the particle size of mullite ceramic balls is 250 mesh, the monofilament diameter of mullite fiber is 4um, and the short cut length is 0.9mm;

[0035] S4: spray the tough layer 2 slurry evenly on the outer wall of the casing body 1, with a spraying rate of 40 cm / s and a spraying time of 40 min. Dry the casing after spraying at 50° C. for 24 h to obtain a casing body 1 containing a tough layer 2, wherein the thickness of the tough layer 2 is 3 mm;

[0036] S5: spraying glaze inside and outside the sleeve blank 1 containing the tough layer 2, and obtaining a glaze blank after drying;

[0037] S6: sintering the glaze blank at 1280°C for 6 hours to obtain a sleeve containing a strong and tough layer 2.

[0038] In this embodiment, the raw materials of the tough layer 2 are prepared by using mullite additives of different morphologies, rather than directly introduced into the base of the casing material. On the one hand, the uneven distribution of the components in the base when the additives are directly introduced is effectively improved, and the reliability of the casing is improved; a good bonding interface can be formed between the tough layer 2 and the casing blank 1. When the crack expands to the interface, the crack can deflect, expand and branch at the interface to consume the power of crack expansion, thereby improving the toughness of the material; on the other hand, the preparation of the tough layer 2 in the casing improves the safety of the casing. When the casing explodes, the continuous network formed by the tough layer 2 can effectively restrain the destruction of the casing blank 1 and limit the explosion damage of the casing blank 1. The introduction of mullite and the preparation of the tough layer 2 simultaneously solve the phase composition design, microstructure design and porcelain sleeve structure design of the casing, and the casing toughness is improved under the synergistic effect from the phase composition to the macro-microstructure design, thereby overcoming the enhancement effect of the casing toughening effect under a single strategy. The casing containing the mullite toughening layer in this embodiment is measured by the single-side notched beam method and the fracture toughness is 8.7 MPa·m 1 / 2 .

[0039] Embodiment 2:

[0040] like Figure 1As shown, a sleeve containing a mullite strengthening layer comprises a sleeve blank 1 with a hollow tubular structure, the outer wall of the sleeve blank 1 is coated with a strengthening layer 2, the inner wall of the sleeve blank 1 is coated with a glaze layer 3, and the side of the strengthening layer 2 away from the sleeve blank 1 is coated with the glaze layer 3; the thickness of the strengthening layer 2 is 2 mm; the strengthening layer 2 is composed of mullite powder, mullite ceramic balls and mullite fibers in a mass ratio of 6:6-11:3-8, and the mass ratio of mullite powder, mullite ceramic balls and mullite fibers contained in the strengthening layer 2 in this embodiment is 3:4:3.

[0041] The toughening layer 2 in this embodiment is composed of mullite powder, mullite ceramic balls, and mullite fibers with different morphological characteristics to form a complex, continuous, multi-scale mullite bonding network, which ensures the stability of the introduced mullite phase and micromorphology and improves the controllability of the introduced toughening phase composition and content.

[0042] The method for preparing a casing containing a mullite toughening layer in this embodiment comprises the following specific steps:

[0043] S1: The raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and the casing blank 1 is obtained by wet ball milling, spray granulation, cold isostatic pressing, blank trimming, and drying;

[0044] S2: With silica sol as a binder, 1.2% of sodium humate, 0.25% of polycarboxylic acid high-efficiency water reducer, 0.6% of hydroquinone, 0.2% of polyether-modified silicone, and 0.3% of potassium sodium tartrate were added to the silica sol in sequence, and the mixture was mechanically stirred at 1500 rpm for 10 min to obtain a premixed solution;

[0045] S3: Mullite powder, mullite ceramic balls and mullite fibers are added in a mass ratio of 3:4:3 to the obtained premixed solution, and mechanically stirred at a speed of 1500 rpm for 10 minutes to obtain a tough layer 2 slurry; wherein the mass ratio of silica sol to the total weight of mullite powder, mullite ceramic balls and mullite fibers is 1:5; the particle size of mullite powder is 600 mesh, the particle size of mullite ceramic balls is 200 mesh, the monofilament diameter of mullite fiber is 3um, and the short cut length is 0.8mm;

[0046] S4: spray the tough layer 2 slurry evenly on the outer wall of the casing body 1, with a spraying rate of 40 cm / s and a spraying time of 40 min. Dry the casing at 50° C. for 24 h to obtain a casing body 1 containing a tough layer 2, wherein the thickness of the tough layer 2 is 2 mm.

[0047] S5: spraying glaze inside and outside the sleeve blank 1 containing the tough layer 2, and obtaining a glaze blank after drying;

[0048] S6: sinter the glaze blank at 1260°C for 5 hours to obtain a sleeve containing a strong and tough layer 2.

[0049] In this embodiment, the raw materials of the tough layer 2 are prepared by using mullite additives of different morphologies, rather than directly introduced into the base of the casing material. On the one hand, the uneven distribution of the components in the base when the additives are directly introduced is effectively improved, and the reliability of the casing is improved; a good bonding interface can be formed between the tough layer 2 and the casing blank 1. When the crack expands to the interface, the crack can deflect, expand and branch at the interface to consume the power of crack expansion, thereby improving the toughness of the material; on the other hand, the preparation of the tough layer 2 in the casing improves the safety of the casing. When the casing explodes, the continuous network formed by the tough layer 2 can effectively restrain the destruction of the casing blank 1 and limit the explosion damage of the casing blank 1. The introduction of mullite and the preparation of the tough layer 2 simultaneously solve the phase composition design, microstructure design and porcelain sleeve structure design of the casing, and the casing toughness is improved under the synergistic effect from the phase composition to the macro-microstructure design, thereby overcoming the enhancement effect of the casing toughening effect under a single strategy. The casing containing the mullite toughening layer in this embodiment is measured by the single-side notched beam method and the fracture toughness is 6.8 MPa·m 1 / 2 .

[0050] Embodiment 3:

[0051] like Figure 1 As shown, a sleeve containing a mullite strengthening layer comprises a sleeve blank 1 with a hollow tubular structure, the outer wall of the sleeve blank 1 is coated with a strengthening layer 2, the inner wall of the sleeve blank 1 is coated with a glaze layer 3, and the side of the strengthening layer 2 away from the sleeve blank 1 is coated with the glaze layer 3; the thickness of the strengthening layer 2 is 2 mm; the strengthening layer 2 is composed of mullite powder, mullite ceramic balls and mullite fibers in a mass ratio of 6:6-11:3-8, and the mass ratio of mullite powder, mullite ceramic balls and mullite fibers contained in the strengthening layer 2 in this embodiment is 3:3:4.

[0052] The toughening layer 2 in this embodiment is composed of mullite powder, mullite ceramic balls, and mullite fibers with different morphological characteristics to form a complex, continuous, multi-scale mullite bonding network, which ensures the stability of the introduced mullite phase and micromorphology and improves the controllability of the introduced toughening phase composition and content.

[0053] The method for preparing a casing containing a mullite toughening layer in this embodiment comprises the following specific steps:

[0054] S1: The raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and the casing blank 1 is obtained by wet ball milling, spray granulation, cold isostatic pressing, blank trimming, and drying;

[0055] S2: Using silica sol as a binder, 2.5% of sodium humate, 0.4% of polycarboxylic acid high-efficiency water reducer, 1.1% of hydroquinone, 0.35% of polyether modified silicone, and 0.6% of potassium sodium tartrate were added to the silica sol in sequence, and the mixture was mechanically stirred at 2000 rpm for 15 minutes to obtain a premixed solution;

[0056] S3: Mullite powder, mullite ceramic balls and mullite fibers are added in a mass ratio of 3:3:4 to the obtained premixed solution, and mechanically stirred at a speed of 2000 rpm for 20 minutes to obtain a tough layer 2 slurry; wherein the mass ratio of silica sol to the total weight of mullite powder, mullite ceramic balls and mullite fibers is 1:5; the particle size of mullite powder is 1000 mesh, the particle size of mullite ceramic balls is 300 mesh, the monofilament diameter of mullite fiber is 5um, and the short cut length is 1mm;

[0057] S4: spray the tough layer 2 slurry evenly on the outer wall of the casing body 1, with a spraying rate of 50 cm / s and a spraying time of 50 min. Dry the casing at 50° C. for 24 h to obtain a casing body 1 containing a tough layer 2, wherein the thickness of the tough layer 2 is 5 mm.

[0058] S5: spraying glaze inside and outside the sleeve blank 1 containing the tough layer 2, and obtaining a glaze blank after drying;

[0059] S6: sintering the glaze blank at 1300° C. for 7 hours to obtain a sleeve containing a tough layer 2.

[0060] In this embodiment, the raw materials of the tough layer 2 are prepared by using mullite additives of different morphologies, rather than directly introduced into the base of the casing material. On the one hand, the uneven distribution of the components in the base when the additives are directly introduced is effectively improved, and the reliability of the casing is improved; a good bonding interface can be formed between the tough layer 2 and the casing blank 1. When the crack expands to the interface, the crack can deflect, expand and branch at the interface to consume the power of crack expansion, thereby improving the toughness of the material; on the other hand, the preparation of the tough layer 2 in the casing improves the safety of the casing. When the casing explodes, the continuous network formed by the tough layer 2 can effectively restrain the destruction of the casing blank 1 and limit the explosion damage of the casing blank 1. The introduction of mullite and the preparation of the tough layer 2 simultaneously solve the phase composition design, microstructure design and porcelain sleeve structure design of the casing, and the casing toughness is improved under the synergistic effect from the phase composition to the macro-microstructure design, thereby overcoming the enhancement effect of the casing toughening effect under a single strategy. The casing containing the mullite toughening layer in this embodiment has a fracture toughness of 7.3 MPa·m after being measured by the single-side notched beam method. 1 / 2 .

[0061] Comparative Example 1:

[0062] This comparative example is a method for preparing a sleeve, and the specific operating steps are as follows:

[0063] S1: The raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and the casing blank 1 is obtained by wet ball milling, spray granulation, cold isostatic pressing, blank trimming, and drying;

[0064] S2: spraying glaze on the inside and outside of the sleeve blank 1, and obtaining a glaze blank after drying;

[0065] S3: sintering the glaze blank at 1280° C. for 6 hours to obtain a sleeve.

[0066] The casing of this comparative example has a fracture toughness of 5.2 MPa·m after being measured by the single-side notched beam method. 1 / 2 .

[0067] Comparative Example 2:

[0068] This comparative example is a method for preparing a casing containing a mullite additive, and the specific operating steps are as follows:

[0069] S1: The raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and 5% of the total amount of the raw materials is added with mullite powder, and the casing blank is obtained by wet ball milling, spray granulation, cold isostatic pressing, blank trimming, and drying;

[0070] S2: spraying glaze inside and outside the sleeve blank, and obtaining a glaze blank after drying;

[0071] S3: sintering the glaze blank at 1280° C. for 6 hours to obtain a sleeve containing a mullite additive.

[0072] The casing containing mullite additive in this comparative example has a fracture toughness of 5.9 MPa·m after being measured by the single-side notched beam method. 1 / 2 .

[0073] Comparative Example 3:

[0074] This embodiment provides a method for preparing a casing containing a mullite tough layer. This comparative embodiment is partially the same as embodiment 1, except that:

[0075] The particle size of the mullite powder used is 400 mesh, the particle size of the mullite ceramic ball is 150 mesh, the diameter of the single filament of the mullite fiber is 2um, and the short cut length is 2mm.

[0076] The casing of this comparative example containing a mullite toughening layer has a fracture toughness of 6.3 MPa·m after being measured by the single-side notched beam method. 1 / 2 .

[0077] Comparative Example 4:

[0078] This embodiment provides a method for preparing a casing containing a mullite tough layer. This comparative embodiment is partially the same as embodiment 1, except that:

[0079] The particle size of the mullite powder used is 1200 mesh, the particle size of the mullite ceramic ball is 400 mesh, the diameter of the single filament of the mullite fiber is 6um, and the short cut length is 2mm.

[0080] The casing of this comparative example containing a mullite tough layer has a fracture toughness of 6.5 MPa·m after being measured by the single-side notched beam method. 1 / 2 .

[0081] The comparison of the fracture toughness of the casing prepared by the methods of Examples 1-3 and Comparative Examples 1-4 is shown in Table 1 below:

[0082] Table 1 Comparison of the fracture toughness of the casing prepared in Examples 1-3 and Comparative Examples 1-4

[0083]

[0084] By comparing the fracture toughness of the casing prepared by the methods of Examples 1-3 and Comparative Examples 1-2 after measuring them by the single-side notched beam method, it can be concluded that the casing prepared by the methods of Examples 1-3 has higher fracture toughness. It can be seen that the casing prepared by not containing mullite additives and directly adding mullite additives to the casing blank has poorer toughness than the casing prepared by the strong and tough layer 2 of the present invention alone.

[0085] In addition, compared with Examples 3-4, the particle sizes of mullite powder, mullite ceramic balls and mullite fibers used to prepare the tough layer 2 in Examples 1-3 are different, which affects the toughness of the casing. The present invention preferably uses the mullite powder particle size used in Examples 1-3.

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A casing containing a mullite tough layer, characterized in that: A sleeve blank having a hollow tubular structure, wherein a tough layer is coated on the outer wall of the sleeve blank, a glaze layer is coated on the inner wall of the sleeve blank, and a glaze layer is coated on the outer side of the tough layer; the tough layer is composed of mullite powder, mullite ceramic balls and mullite fibers in a mass ratio of 6:6-11:3-8; The method for preparing the sleeve specifically comprises the following steps: S1: preparing a casing blank, wherein the raw material ratio is recorded as 49% bauxite, 19% potassium feldspar, 11% kaolin, and 21% clay in terms of mass percentage, and the casing blank is obtained by wet ball milling, spray granulation, cold isostatic pressing, blanking, and drying; S2: Using silica sol as a binder, 1.2-2.5% of sodium humate, 0.25-0.4% of polycarboxylic acid high-efficiency water reducer, 0.6-1.1% of hydroquinone, 0.2-0.35% of polyether modified silicone, and 0.3-0.6% of potassium sodium tartrate are sequentially added to the silica sol, and mechanically stirred at a speed of 1500-2000 rpm for 10-15 minutes to obtain a premixed solution; S3: adding mullite powder with a particle size of 600-1000 mesh, mullite ceramic balls with a particle size of 200-300 mesh, and mullite fibers with a monofilament diameter of 3-5 μm and a short cut length of ≤1 mm to the premixed solution in a mass ratio of 6:6-11:3-8, and mechanically stirring at a speed of 1500-2000 rpm for 10-20 min to obtain a tough layer slurry, wherein the mass ratio of the silica sol to the total weight of the mullite powder, mullite ceramic balls and mullite fibers is 1:5; S4: spray the tough layer slurry evenly on the outer wall of the casing blank at a spraying rate of 30-50 cm / s and a spraying time of 30-50 min, and dry the sprayed casing at 50° C. for 24 h to obtain a casing blank containing a tough layer; S5: spraying glaze inside and outside the sleeve blank containing the tough layer, and obtaining a glaze blank after drying; S6: sintering the glaze blank at 1260°C-1300°C for 5-7 hours to obtain a sleeve containing a strong and tough layer.

2. The casing containing a mullite toughening layer according to claim 1, characterized in that: The thickness of the tough layer is 2-5 mm.

Citation Information

Patent Citations

  • Production method of porcelain core composite insulator

    CN105913983A

  • Fabrication method of aluminum oxide porcelain core composite insulator

    CN108305734A